Accumulation of phosphatidylcholine on gut mucosal surface is not dominated by electrostatic interactions - Korytowski, Agatha Anna; Abuillan, Wasim; Amadei, Federico; Makky, Ali; Gumiero, Andrea; Sinning, Irmgard; Gauss, Annika; Stremmel, Wolfgang; Tanaka, Motomu (Biochimica et biophysica acta. Biomembranes, 2017)
The accumulation of phosphatidylcholine (PC) in the intestinal mucus layer is crucial for the protection of colon epithelia from the bacterial attack. It has been reported that the depletion of PC is a distinct feature of ulcerative colitis. Here we addressed the question how PC interacts with its binding proteins, the mucins, which may establish the hydrophobic barrier against colonic microbiota. In the first step, the interactions of dioleoylphosphatidylcholine (DOPC) with two mucin preparations from porcine stomach, have been studied using dynamic light scattering, zeta potential measurement, and Langmuir isotherms, suggesting that mucin binds to the surface of DOPC vesicles. The enthalpy of mucin-PC interaction could be determined by isothermal titration calorimetry. The high affinity to PC found for both mucin types seems reasonable, as they mainly consist of mucin 2, a major constituent of the flowing mucus. Moreover, by the systematic variation of net charges, we concluded that the zwitterionic DOPC has the strongest binding affinity that cannot be explained within the electrostatic interactions between charged molecules.
Available online 15 February 2017
Gesehen am 25.10.2018